A Sociotechnical History of the Ultralightweight Wheelchair: A Vehicle of Social Change. (November 2020) - Stewart, Hilary; Watson, Nick
The emergence of the ultralightweight wheelchair has transformed the lives of millions of disabled people. It has radically changed the principles and practices of wheelchair design, manufacture, and prescription and redefined wheelchair users and wheelchair use. Designed and built largely by wheelchair users themselves, it was driven initially by a desire to improve sport performance and later by a wish for improved access to the community and built environment. In this paper, we draw on oral histories and documentary sources to reconstruct its sociotechnical history. We employ the analytical concept of "boundary object" to illuminate how the wheelchair as a technological artifact is implicated in relations of social change and show the role of wheelchair users in the development and emergence of the ultralightweight wheelchair. We highlight the tensions and negotiations within this history and the push and pull between different social groups. The emergence of the ultralightweight wheelchair helped to reconfigure ideas about wheelchairs and their users and allowed wheelchairs to gain a foothold within broader social and technological infrastructures. What makes this account powerful is that this is a success story for a group who have historically been excluded from design processes.